Association between triglyceride-glucose index and chronic kidney disease: A cohort study and meta-analysis - Ren, Xiao; Jiang, Minglan; Han, Longyang; Zheng, Xiaowei (Nutrition, metabolism, and cardiovascular diseases, 2023)
Nowadays, the relationship between triglyceride-glucose (TyG) index and chronic kidney disease (CKD) is still controversial. We aimed to prospectively investigate the relationship between TyG index and CKD in a cohort and meta-analysis. A total of 10498 participants from the China Health and Retirement Longitudinal Study (CHARLS) were included. Participants were divided into four groups based on the quartiles of the TyG index. CKD was based on self-reported physicians’ diagnosis or personal eGFR level. A cox regression model was established to analyze the correlation between TyG index and CKD. A meta-analysis was conducted to incorporate the results of the current study and previous studies on the association of TyG index with CKD. In multivariable-adjusted analyses, the adjusted hazard ratio (95% confidence interval) for the highest versus lowest quartile of TyG index was 1.30 (1.08–1.57). Each 1-SD higher TyG index was associated with an increased risk of 11% (HR 1.11, 95% CI 1.03–1.19). The meta-analysis further confirmed the significant associations between TyG and CKD and pooled relative risk for highest vs lowest TyG index quartile was 1.47 (1.32–1.63). Higher TyG index was associated with increased risk of CKD, independently of established risk factors. The TyG index may be a predictor of incident CKD. •Chronic kidney disease increased the burden on the economy and medical resources.•A cohort study found that higher TyG index was associated with increased risk of CKD.•Meta-analysis further confirmed that the TyG index may be a predictor of CKD.•TyG index can be used as an predictive tool to find individuals with high risk of CKD.